Cautiously optimistic: A survey of radiation oncology professionals' perceptions of automation in radiotherapy planning. (December 2020) - Batumalai, Vikneswary; Jameson, Michael G.; King, Odette; Walker, Rhiannon; Slater, Chelsea; Dundas, Kylie; Dinsdale, Glen; Wallis, Andrew; Ochoa, Cesar; Gray, Rohan; Vial, Phil; Vinod, Shalini K.
Highlights: Majority of respondents felt automation will improve consistency, productivity and quality of planning. 27% of respondents believe automation will reduce job satisfaction. Majority of respondents (71%) thought that automation will cause a loss of skills. This study highlights the need for continued education to ensure that skills and knowledge are not lost with automation. Abstract: Introduction: While there is evidence to show the positive effects of automation, the impact on radiation oncology professionals has been poorly considered. This study examined radiation oncology professionals' perceptions of automation in radiotherapy planning. Method: An online survey link was sent to the chief radiation therapists (RT) of all Australian radiotherapy centres to be forwarded to RTs, medical physicists (MP) and radiation oncologists (RO) within their institution. The survey was open from May-July 2019. Results: Participants were 204 RTs, 84 MPs and 37 ROs (response rates ∼10% of the overall radiation oncology workforce). Respondents felt automation resulted in improvement in consistency in planning (90%), productivity (88%), quality of planning (57%), and staff focus on patient care (49%). When asked about perceived impact of automation, the responses were; will change the primary tasks of certain jobs (66%), will allow staff to do the remaining components of their job more effectively (51%), will eliminate jobs (20%), and will not have an impact on jobs (6%). 27% of respondents believe automation will reduce job satisfaction. 71% of respondents strongly agree/agree that automation will cause a loss of skills, while only 25% strongly agree/agree that the training and education tools in their department are sufficient. Conclusion: Although the effect of automation is perceived positively, there are some concerns on loss of skillsets and the lack of training to maintain this. These results highlight the need for continued education to ensure that skills and knowledge are not lost with automation.